The Pricing of Multiple Line P&C Insurance Based on the Full Information Underwriting Beta - Zhang, Li; Nielson, Norma (Assurances et gestion des risques / Insurance and Risk Management, 2009)
This paper develops a financial model of insurance pricing that is able to price insurance by line in a multi-line property & casualty insurance company based on the Full Information Underwriting Beta Methodology. It extends the existing literature in insurance pricing in that the model is suitable for multi-line pricing and reflects the systematic risk of different business lines. Based on Canadian Property & Casualty insurance industry data, the primary empirical findings in this paper strongly reject the argument in prior studies that underwriting betas of distinct lines vary in proportion to the length of the period that the premium of the corresponding line can be kept for investment. The results also show that the expected underwriting profit margin of liability insurance is the lowest among three distinct business lines: auto insurance, property insurance, and liability insurance.